„Szent marginalitás”: Egy csereháti Mária-jelenés lokális emlékezetének vizsgálata - Szabó, Elemér (Studia Litteraria, 2018)
The subject of my paper, the documentary titled The Treasures of Attila reveals an event, during which a bell-ringer of a small village of Cserehát rebuilds a tiny wooden chapel in the heart of the woods, on the spot of an earlier Virgin Mary apparition that once had been a debated issue, but has been long forgotten since. Attila’s private venture ends up in a communal pilgrimage to the chapel and the consecration of the building. The paper reveals Attila’s identity strategy which guides him to set up this place of memory and religious worship. In the gesture of the chapel’s erection he defines himself as the guard of the forgotten memory and the protector of values that have been wasted by others. The paper also describes the communicative memory of the former miracle-event as overburdened by conflicts, because of the exclusion and legitimation struggle to which the apparition narrative is subject. This struggle is attached to several authorities (state, church) and local social groups. In relation to the erection of the chapel as a memorial, the fragmentary image of communicative memory has been succeeded by a more settled remembrance typical of cultural memory.